Diagnostiek en behandeling van volwassenen met een HIV-infectie - Danner, S.A.; Meenhorst, P.L.; Pauw, W. (Houten: Bohn Stafleu Van Loghum, 1992)
"S.A. Danner; P.L. Meenhorst; W. Pauw... et al. Fonds Suzan Daniel (FSD)"